Bioconversion of Garcinia mangostana rind extract juice with yeast fermentation: Impact on its key bioactivity - Di Menna, Dalila; Buranavanitvong, Natthanan; Prakitchaiwattana, Cheunjit (Food Agricultural Sciences and Technology, 2024)
Mangosteen (Garcinia mangostana L.) peel, a by-product of fruit processing, contains bioactive polyphenols with potential health benefits. However, the consumption of mangosteen peel as a supplement is generally limited due to its astringent taste. This study proposed the process for adding value the Garcinia mangostana rind extract juice (GREj) by bioconversion with yeast fermentation. The GREj was extracted by hydraulic pressing machine. The GREj medium was formulated by diluting with water to contain 20% GREj adjusted total soluble solids (TSS) with sugar to 12.00 °Brix and pH to 4.00 with lactic acid. After fermentation 3L of GREj medium with Saccharomyces cerevisiae in 5L bioreactor, the composition of GREj evaluated through HPLC (High Performance Liquid Chromatography) and TLC (thin layer chromatography) were significantly changed. The main acid of GREj, acetic acid was found greater than citric acid, the migration pattern on TLC with retention factor (Rf) was changed from 0.24 to 0.26. The antioxidant; DPPH (2,2-diphenyl-1-picrylhydrazyl) and TPC (total phenolic content) demonstrated the significant improvement of the GREj antioxidant capacity. The fermented GREj had intense red-purple color with fermented aroma and sour taste. This fermented juice could be further developed to be a functional drink as well as processed to be a powder form to use as functional ingredient and/or supplement. This demonstrated that yeast fermentation could be a potential mean in value adding of mangosteen peel from being agricultural waste to functional beverages and meals.